The influence of executive functions on spatial biases varies during the lifespan - Takio F; Koivisto M; Hamalainen H (Elsevier Ltd, 2022)
Many perceptual processes, such as language or face perception, are asymmetrically organised in the hemispheres already in childhood. These asymmetries induce behaviourally observable spatial biases in which the observer perceives stimuli in one of the hemispaces more efficiently or more frequently than in the other one. Another source for spatial biases is spatial attention which is also asymmetrically organised in the hemispheres. The bias induced by attention is directed towards the right side, which is clearly demonstrated by patients with neglect but also in lesser degree by healthy observers in cognitively loading situations. Recent findings indicate that children and older adults show stronger spatial biases than young adults. We discuss how the development of executive functions might contribute to the manifestation of spatial biases during the lifespan. We present a model in which the interaction between the asymmetrical perceptual processes, the age-related development of the lateralised spatial attention and the development of the executive functions influence spatial perceptual performance and in which the development and decline of the executive processes during the lifespan modify the spatial biases. (C) 2014 The Authors. Published by Elsevier Ltd. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/3.0/.)